Electrochemically Synthesized Silver Nanoparticles Are Active Against Planktonic and Biofilm Cells of Pseudomonas aeruginosa and Other Cystic Fibrosis-Associated Bacterial Pathogens - Pompilio, Arianna; Geminiani, Cristina; Bosco, Domenico; Rana, Rosalba; Aceto, Antonio; Bucciarelli, Tonino; Scotti, Luca; Di Bonaventura, Giovanni (Frontiers in Microbiology, 2018)
A novel, electrochemically synthesized, silver nanoparticles (AgNPs) formulation was evaluated in vitro against P.aeruginosa, B.cepacia, S.maltophilia and S.aureus strains from cystic fibrosis (CF) patients. AgNPs were particularly active against P.aeruginosa and B.cepacia planktonic cells (median MIC: 1.06 and 2.12 µg/ml, respectively) by a rapid, bactericidal and concentration-dependent effect. AgNPs showed to be particularly effective against P.aeruginosa and S.aureus biofilm causing a viability reduction ranging from 50% (1xMIC) to >99.9% (4xMIC). Electron microscopy showed that AgNPs deconstruct extracellular matrix of P.aeruginosa biofilm, and accumulate at the cell surface causing cell death secondary to membrane damage. Compared to tobramycin, AgNPs showed comparable, or even better, activity against planktonic and biofilm P.aeruginosa cells. AgNPs at concentrations effective against B.cepacia and P.aeruginosa were not toxic to G.mellonella larvae. Our silver-based formulation might be an alternative to antibiotics in CF patients. Further in vitro and in vivo studies are warranted to confirm this therapeutic potential.